2019
DOI: 10.1080/24704067.2019.1566755
|View full text |Cite
|
Sign up to set email alerts
|

Spectator Sport and Population Health: A Consultation with U.S. College Athletics Employees

Abstract: A growing number of studies have been published to understand how spectator sport may influence the health of a population. However, it is unknown if these studies address research questions relevant to professionals engaging in the promotion of spectator sport. We conducted a web-based survey with 136 practitioners employed in U.S. college athletics to identify their research priorities and needs regarding spectator sport's influence on population health. The combination of qualitative and quantitative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Coincidently, these three themes were the most frequently examined themes based on Inoue et al's (2019) follow-up review of articles that were published in premier sport management journals from 2014 to 2018, pointing to convergence between the interests of sport management practitioners and those of researchers. However, the results also revealed some divergence: the theme of "event's impact on physical impairment and mortality," which was the most researched theme according to Inoue, Berg, et al's (2015, p. 712) scoping review, was deemed least important by college athletics employees (Inoue et al, 2019). Second, employees' qualitative responses indicated that they defined the concept of population health more broadly than the conventional definition above (Inoue et al, 2019).…”
Section: Spectator Sport and Population Health Researchmentioning
confidence: 96%
See 3 more Smart Citations
“…Coincidently, these three themes were the most frequently examined themes based on Inoue et al's (2019) follow-up review of articles that were published in premier sport management journals from 2014 to 2018, pointing to convergence between the interests of sport management practitioners and those of researchers. However, the results also revealed some divergence: the theme of "event's impact on physical impairment and mortality," which was the most researched theme according to Inoue, Berg, et al's (2015, p. 712) scoping review, was deemed least important by college athletics employees (Inoue et al, 2019). Second, employees' qualitative responses indicated that they defined the concept of population health more broadly than the conventional definition above (Inoue et al, 2019).…”
Section: Spectator Sport and Population Health Researchmentioning
confidence: 96%
“…The ability for the field to evolve is recognized as necessary for sport management's continued advancement, relevance, and prospects for interdisciplinary collaboration (Chalip, 2006;Chalip et al, 2010;Costa, 2005;Doherty, 2012). For instance, the role sport may have in promoting the health of the population, or population health, has been widely examined by sport management scholars (Berg et al, 2015;Chalip, 2006;Edwards & Rowe, 2019;Inoue et al, 2019;Inoue, Berg et al, 2015;Rowe et al, 2013). One significant subtopic within the sport and population health discourse is understanding the relationship between spectator sport-sport and athletic events provided as entertainment for consumers (Chelladurai, 2014)-and population health.…”
Section: "Sport Is Double-edged": a Delphi Study Of Spectator Sport A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Calls for addressing grand challenges in organizational and management research have strongly resonated. Research under the label has proliferated – from topics we would expect like climate change, pollution, and inequality (e.g., Mair et al, 2016; Porter et al, 2020; Wright and Nyberg, 2017), to less expected ones like sport and population health (Inoue et al, 2019). With this explosion of activity, organizational scholars have used the grand challenges label in different ways, which some argue risks ‘conflat[ing] qualitatively distinct types of phenomena, levels of analysis, and scales/scopes of issues’, potentially lessening the work’s impact (Brammer et al, 2019, p. 518).…”
Section: The Nature and Origin Of Grand Challengesmentioning
confidence: 99%